واقع التدريب المهني لدى عمال مؤسسة النسيج بالأغواط - شمة ابراهيم; بن منصور عبد القادر; عمومن رمضان (My University, 2019)
The study aimed to identify the reality of vocational training from the point of view of the workers of the National Society of Textiles in LAGHOUAT and to understand the importance of the differences in the preparation of vocational training from the point of view of the members of the sample, by sex, occupational specialization and seniority at work. A sample of (66) workers and workers selected at random by the company National de Textile, where we obtained the following results:  Vocational training is important from the point of view of the workers of the National Textile Society in LAGHOUAT.  The importance of preparation for vocational training differs from the point of view of the workers of the National Textile Company of LAGHOUAT, according to the different specializations for. the benefit of the group of spinning workers.  The importance of preparation for vocational training differs from the point of view of the workers of the National Textile Company of LAGHOUAT, according to the different specializations for the benefit of the group of spinning workers. The importance of preparation for vocational training does not differ from the point of view of the workers of the National Textile Company in LAGHOUAT according to the seniority of the work